2019
DOI: 10.18805/lr-4165
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Diversity of Pea Genotypes (Pisum sativum L.) Based on Multivariate Analysis

Abstract: The present study was conducted to identify the nature and magnitude of genetic divergence among fifty five genotypes based on phenotypical traits using the multivariate analysis. Based on cluster analysis, the genotypes were best fitted into six clusters. The maximum and minimum genotypes grouped in cluster III (14) and minimum were in Cluster IV (4) respectively. The maximum intra-cluster distance was shown by cluster I (D2 2.543) indicating maximum difference among the genotypes within and the minimum value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The results of our Kruskal-Wallis test executed on 29 continuous quantitative traits showed a significant effect of the factor (accessions) for all the attributes used in our study (Table 1). These genetically diverse accessions can be used as promising parents for hybridization (Singh et al 2021), to develop superior hybrids with desirable combination of traits (Janghel et al 2021). Mebarkia et al (2020) revealed a significant positive relationship between the full flowering stage with grain yield (r=0.76) and aerial biomass (r=0.69) and showed that late varieties are the most productive.…”
Section: Resultsmentioning
confidence: 99%
“…The results of our Kruskal-Wallis test executed on 29 continuous quantitative traits showed a significant effect of the factor (accessions) for all the attributes used in our study (Table 1). These genetically diverse accessions can be used as promising parents for hybridization (Singh et al 2021), to develop superior hybrids with desirable combination of traits (Janghel et al 2021). Mebarkia et al (2020) revealed a significant positive relationship between the full flowering stage with grain yield (r=0.76) and aerial biomass (r=0.69) and showed that late varieties are the most productive.…”
Section: Resultsmentioning
confidence: 99%
“…Jaccard's similarity index was ranged from 0.589 between accessions ' maximally to a genetic divergence of pea (Cupic et al, 2009;Suman et al, 2019;Singh et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…In peas, various genetic diversity studies were done using phenotypic traits (Priyanka and Lal, 2021;Singh et al, 2021a). Loridon et al (2005) initially developed a set of SSRs for genetic diversity and linkage mapping of a pea.…”
Section: Introductionmentioning
confidence: 99%